Out-of equilibrium bids in auctions: wrong expectations or wrong bids - Oliver Kirchkamp; J. Philipp Reiss (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Deviations from equilibrium bids in auctions can be related to inconsistent expectations with correct best replies (see Eyster and Rabin, 2005; Crawford and Iriberri, 2007) or correct expectations but small (perhaps quantal-response) mistakes in best replies (see Goeree et al., 2002). To distinguish between these two explanations we use a novel experimental procedure and study expectations together with best replies. We extensively test the internal validity of this setup. We find that deviations from equilibrium bids do not seem to be due to wrong expectations but due to deviations from a best reply.
Keywords: C92; D44; 330; Experiments; Auction; Expectations; Auktionstheorie; Gleichgewicht; Erwartungstheorie; Test